Comunicação pública e gestão de crise da Covid-19 em prefeituras do Rio Grande do Sul - Ganasini, Milena (2023)
This study focuses on public communication during crisis management in the context of the Coronavirus pandemic. For approximately two years, the world has lived with a health crisis, with economic, political and social dimensions resulting from the virus, scientifically called SARS-CoV-2 (COVID-19). The restrictions imposed by the Coronavirus composed the world scenario, unquestionably changing people's daily lives and way of life. The pandemic demanded a strong response from the Public Administration and raised the communication of public institutions to another level, since municipalities were given the lead in relation to the operationalization of State actions to combat the Coronavirus crisis. Through this research, an analysis is proposed on the performance of municipal governments in relation to communication actions, especially strategies on digital platforms, implemented during the COVID-19 crisis. Based on this scenario, the established research question is whether the principles defended by public communication in the municipalities of Rio Grande do Sul with a population between 200 and 400 thousand inhabitants were maintained during the COVID-19 crisis. The main objective of the study is to identify the public communication actions carried out by four city halls in the state of Rio Grande do Sul. In addition, it aims to compare the actions developed in official digital media, identify the communication principles and approaches adopted in crisis management and presents an infographic of public communication performance for these municipalities. This is a descriptive research with a qualitative approach that had as methodology the study of multi-cases. Through the bibliographic research carried out, the theme of crises and also public communication is addressed. This work was developed from the observation and content analysis of 2,173 publications, including posts on Facebook and Instagram pages, and the titles of articles published on the institutional website of the City Halls of Canoas, Gravataí, Pelotas and Santa Maria, in the state of Rio Grande do Sul, in two different periods, considering the turning point of the crisis in 2020 and 2021. The results show that the crisis management received similar administrative responses in all municipalities and indicate that there was an imbalance between the categories of public communication used by municipalities during the COVID-19 crisis, with the prevalence of communication actions characterized by Duarte (2007) as information instruments to the detriment of dialogue instruments, indicating the prevalence of a utilitarian and instrumental view of communication.